Art Interventions and Disruptions in Financial Systems: An Interview with Paolo Cirio. (3rd April 2018) - Lerer, Marisa; McGarrigle, Conor
Abstract : Prior to the release of the 2016 Panama Papers and 2017 Paradise Papers – leaked documents that uncovered the movement of funds through offshore tax havens – conceptual artist Paolo Cirio's (b. 1979) project Loophole for All (2013) revealed and documented the mechanics behind offshore financial centers. In this interview, Cirio expounds upon his investigations of offshore banking practices, describes his projects for instituting alternative financial models, and explains his hacktivist (i.e. Internet activist) strategies that engage with legal and economic systems. Defining the foundational movements that inform his work, Cirio in turn illuminates his methods of direct provocation and performance to reveal social and economic inequalities.